The Evaluation of Antioxidant and Anticancer Activity of Alfalfa Extract on MCF7 Cell Line - Babakhani, Babak; Houshani, Mahdieh; Motalebi Tala Tapeh, Sogol; Nosratirad, Reza; Shoja Shafiee, Maryam; Heidari keshel, Saeed (Regeneration, Reconstruction & Restoration (Triple R), 2019)
Introduction: The Breast cancer is the second most common cancer in the women. Natural products extracted from medicinal plants can play an important role in cancer treatment. These compounds are probably effective in repairing damaged tissue in cancer. This study was designed to investigate antioxidant activity and cytotoxicity of ethanolic extract of alfalfa on breast cancer MCF7cell line. Materials and Methods: For this purpose, the MCF7 cells line was cultivated and proliferated. Then, the cells exposed to different concentrations of alfalfa (25, 50, 100, 200, and 400 μg/ml) and were incubated for 24, 48, and 72 hours. After the incubation period, the colorimetric MTT method was used to determine cytotoxicity. Also, the total amount of phenol, flavonoid, anthocyanin, and carotenoid as well as the antioxidant activity of the extract were determined. Results: The results showed that the different concentrations of ethanolic extract reduced significantly the growth of cells as compared to that of control (P˂0.05). The most pronounced growth inhibition recorded as 83.74% at the concentration of 400 μg/ml. The extract of alfalfa is a rich source of antioxidant compounds, as phenolics and carotenoid contents of extract were 32.63±0.17 mgGAE/g DW and 33.41±0.22 mg/g FW respectively. Also, its different concentrations affected scientifically on DPPH radical inhibition as the highest inhibitory effect (53.4%) was recorded at concentrations of 3.4 mg of extract. Conclusion: These results suggest that the ethanolic extract of alfalfa have the most antioxidant activity and cytotoxicity against MCF7 cell line. It seems to come with further research, and utilizes its compound in cancer treatment.